Agroforestry Options for Degraded Landscapes in Southeast Asia - Noordwijk, M. van; Ekadinata, A.; Leimona, B.; Catacutan, D.; Martini, E.; Tata, H.L.; Öborn, I.; Hairiah, K.; Wangpakapattanawong, P.; Mulia, R.; Dewi, S.; Rahayu, S.; et al. (Springer, 2020)
In Southeast Asia, 8.5% of the global human population lives on 3.0% of the land area. With 7.9% of the global agricultural land base, the region has 14.7% and 28.9% of such land with at least 10% and 30% tree cover, respectively, and is the worlds’ primary home of ‘agroforests’. Landscapes in the region include the full range of ‘forest transition stages’, as identified in global analysis. A long tradition of top-down national reforestation and tree planting programs has not had success proportional to the efforts and resources allocated. By contrast, farmers in the region have a long tradition of retaining (and managing natural regeneration of) useful trees among planted trees (e.g. tree crops or timber) and annual crops to prevent degradation and avoiding the labour costs of weed control. Meanwhile, state-controlled forests have lost a lot of their diverse tree cover, both legally and illegally. The restoration agenda includes four levels of intensity and stakeholder involvement: (RI) ecological intensification within a land use system; (RII) recovery/regeneration, within a local socioecological system; (RIII) reparation/recuperation, within rules and rewards set by the national policy context; and (RIV) remediation, requiring international support and investment. Major opportunities for restoring the multifunctionality of landscapes in the region are formed by resolution of existing conflicts over multiple claims to ‘forest’ land stewardship. The chapter summarizes lessons learnt in 26 landscapes, grouped in seven ‘degradation syndromes’: Degraded hillslopes, fire-climax grasslands, over-intensified monocropping, forest classification conflicts, drained peatlands, converted mangroves and disturbed soil profiles. It also addresses two overarching concerns: disturbed hydrology and supply sheds at risk. In each landscape, a driver-pressure-state-impact-response analysis of the socioecological system supported a diagnosis beyond the primary degradation symptoms. Appropriate actions reflect six requirements for effective restoration: (1) community involvement, aligned with values and concerns, (2) rights, (3) knowledge and knowhow of sustainable land use practices, (4) markets for inputs (incl. Soil amendments, tree germplasm, labour) and outputs (access, bargaining position), (5) local environmental impacts (often primarily through the water cycle and agrobiodiversity) and (6) global connectivity, including interactions with climate and global biodiversity agendas. All six can be a ‘starting point’ for restoration interventions, but progress is typically limited by several (or all) of the others. In our analysis, all 17 Sustainable Development Goals can contribute to and benefit from a coherent rights-based approach to restoration through agroforestry with specific technologies and choice of species dependent on local context and market access.